Gas Chromatography Mass Spectrometry Analysis of Abutilon Indicum (International Journal of Food and Nutritional Sciences, 2022)
In this study, the bioactive compounds of Abutilon Indicum have beenanalyzed usingGas Chromatography-Mass Spectrometer (GC-MS). The chemical compounds of the whole plant ethanol and aqueous extracts of Abutilon Indicum were investigated using Shimadzu GC-MS.Analysis of Abutilon Indicumwhole plant was carried out after extraction of bioactive compounds in ethanol and aqueousextracts. The compounds identified in alcoholic extract were Salicylic acid methyl and ethyl esters, Steroids, Palmitic acid, Palmitic acid ethyl ester, Myristic acid, Phytol, Linoleic acid ethyl ester, Linolenic acid ethyl and methyl esters and Oleic acid methyl ester having antioxidant activities with anti-inflammatory and anticancer properties.Theexistence of the compoundslike 1,2-Benzendicarboxylic acid diethyl ester and 1,2- Benzenedicarboxylic acid diethyl ester was also identified. Other minor compounds were also identified in the aqueous extract of plant sample by GCMS study which had medicinal value. Bioactive compounds are more in ethanolic extract of plants than in water extracts.